Caught in the middle: the role of the facilities manager in organisational energy use - Goulden, Murray; Spence, Alexa (Elsevier, 2015)
This study analyses the role of the Facilities Manager [FM] as a key actor in organisational energy management. This builds on the idea that ‘middle’ agents in networks can be an important lever for socio-technical change. The study demonstrates the considerable impact the FM can have on workplace energy consumption, whilst identifying a number of factors that constrain their agency and capacity to act. These include demands to meet workforce expectations of comfort; a lack of support from senior management; and a shortage of resources. Underlying these challenges, the study identifies three different energy rationales – that is to say conceptual frameworks – which are deployed by different groups of organisational actors. The challenges of reconciling these at-times-contradictory rationales results in a picture of energy management which to the outsider can appear highly irrational. The paper concludes with a consideration of how policy makers can apply these insights to support energy reduction in workplaces.